Facile synthesis of stable, water soluble, dendron-coated gold nanoparticles. Issue 9 (17th February 2017) - Enciso, Alan E.; Doni, Giovanni; Nifosì, Riccardo; Palazzesi, Ferruccio; Gonzalez, Roberto; Ellsworth, Amy A.; Coffer, Jeffery L.; Walker, Amy V.; Pavan, Giovanni M.; Mohamed, Ahmed A.; Simanek, Eric E.
Abstract : Upon reduction with sodium borohydride, diazonium tetrachloroaurate salts of triazine dendrons yield dendron-coated gold nanoparticles connected by a gold–carbon bond. Abstract : Upon reduction with sodium borohydride, diazonium tetrachloroaurate salts of triazine dendrons yield dendron-coated gold nanoparticles connected by a gold–carbon bond. These robust nanoparticles are stable in water and toluene solutions for longer than one year and present surface groups that can be reacted to change surface chemistry and manipulate solubility. Molecular modeling was used to provide insight on the hydration of the nanoparticles and their observed solubilties.